A new procolophonid (Parareptilia) from the Lystrosaurus Assemblage Zone, Beaufort Group, South Africa - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 2000)
This paper describes the skull of a new genus and species of procolophonid from the Lystrosaurus Assemblage Zone. It is strikingly different from its contemporaries, Procolophon trigoniceps and Owenetta rubidgei, but has a mosaic of characters of each.
Keywords: procolophonid; Triassic; parareptile